APPLICATION OF JEROME BRUNER THEORY TO IMPROVE MATHEMATICSSTUDENT LEARNING OUTCOMES IN CLASS IVB SD NEGERI 158 PEKANBARU - Rani Pratiwi Ningsih; Syahrilfuddin; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The Application of Jerome Bruner's Theory to Improve Mathematics Learning Outcomes of Students in Class IV B of SD Negeri 158 Pekanbaru. This study aims to improve the mathematics learning outcomes of students in class IV B of SD Negeri 158 Pekanbaru by using Jerome Bruner's learning theory. The study was conducted in two cycles. The subjects of this study were all students of class IV B of SD Negeri 158 Pekanbaru, totaling 30 students. While the data collection tool uses test questions, observation sheets. Analysis of the data used with qualitative and quantitative analysis. The results of the study concluded that the application of Jerome Bruner's theory with the steps included: 1) the enactive stage; 2) the iconic stage; 3) symbolic stage, can improve mathematics learning outcomes in class IV B SD Negeri 158 Pekanbaru.